HUBUNGAN TINGKAT RISIKO ERGONOMI DAN BEBAN ANGKUT TERHADAP KELUHAN MUSCULOSKELETAL DISORDERS (MSDs) PADA PABRIK PEMOTONGAN KAYU X MRANGGEN, DEMAK - Bagus Putra Nino; Baju Widjasena; Ekawati Ekawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Cutting activities are activities that cover a variety of manual material handling activities, including lowering, lifting, pushing, pulling, carrying and use of equipment. This work may result in injury if the worker performs activities that exceed his physical capacity. Handle of this material is not only a heavy material handling, but light and small materials when repeated, long duration and incorrect posture can lead to musculoskeletal disorder complaints (MSDs). The purpose of this study was to analyze the correlation between ergonomic risk level of postures and loading weight on musculoskeletal disorder complaints (MSDs). The type of research used is quantitative with observational analytic and cross sectional study. The population of the research were all wood cutting workers in cutting factory which amounted to 30 people with sampling method is total sampling. The data was collected by filling the Body Map sheet for MSDs complaints and measuring the loading weight using the meteran to know the volume and filling out the BRIEF survey sheet to measure the work posture. Data analysis using Chi Square test. The result of hypothesis test shows that there was correlation between ergonomic risk level of right wrist posture (p-value = 0,028), right elbow (p-value = 0,002), left shoulder (p-value = 0,009), right shoulder (p-value = 0,037), neck (p-value = 0.009), back (p-value = 0.013), legs (p-value = 0.027), loading weight(p-value = 0,023, 0,002, 0,023, 0,023, 0,002, 0,008, 0,002, 0,028,0,002) with MSDs complaints. There was no correlation between left wrist (p-value = 0.141) and left elbow (p-value = 0.236) with MSDs complaints of wood cutting workers X Mranggen, Demak. It is recommended for companies to add equipment that facilitates the appointment. For workers to use the correct method when lifting manually.